2017
DOI: 10.25131/gssajg.120.3.341
|View full text |Cite
|
Sign up to set email alerts
|

Rayleigh group velocity extraction from ambient seismic noise to map the south Eastern Cape Karoo region, South Africa

Abstract: The Karoo region of South Africa is an ideal laboratory to use ambient seismic signals to map the shallow subsurface, as it is a quiet and pristine environment with a geology that is relatively well known. Ambient seismic signals were continuously recorded for a ten week period between August and October 2015. The ambient seismic noise network consisted of two groups of 17 temporary, stand-alone seismic stations each. These were installed in the southeastern Cape Karoo region, near the town of Jansenville. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…This area was prioritised mainly due to groundwater and logistical considerations, as well as previous scientific research undertaken by the group, which included studies of black shales from drillholes, deep conductive layer and velocity anomalies. [7][8][9] This led to the deployment of different geophysical methods aimed at better quantifying the deep subsurface, such as magneto-telluric surveys conducted in partnership with the GFZ-Potsdam 3 , and the application of a novel passive seismic technique (i.e. no induced energy) which was only available through AEON-ESSRI at the time.…”
Section: Landowner Suspicions and Trust Buildingmentioning
confidence: 99%
See 1 more Smart Citation
“…This area was prioritised mainly due to groundwater and logistical considerations, as well as previous scientific research undertaken by the group, which included studies of black shales from drillholes, deep conductive layer and velocity anomalies. [7][8][9] This led to the deployment of different geophysical methods aimed at better quantifying the deep subsurface, such as magneto-telluric surveys conducted in partnership with the GFZ-Potsdam 3 , and the application of a novel passive seismic technique (i.e. no induced energy) which was only available through AEON-ESSRI at the time.…”
Section: Landowner Suspicions and Trust Buildingmentioning
confidence: 99%
“…Initial consultations in the survey area primarily focused on providing the local stakeholders of the then Ikwezi Local Municipality (an area now located within the larger Dr Beyers Naude Local Municipality) with an introduction to the Karoo Shale Gas Baseline Research Programme, in order to facilitate initial access to various study sites around the Karoo (see timeline in Figure 1). In Jansenville and across the Noorsveld, prior to commencing with airborne geophysics, the group had already conducted numerous baseline studies, with some still ongoing at the time, including a groundwater survey of 52 boreholes 3,10 , a magneto-telluric ground survey 3,8 , surface ecosystems monitoring in water bodies and termite mounds 3,[11][12][13] , micro-earthquake surveys 5,9 , as well as a household survey 13 in and around Jansenville. On implementation of the magneto-telluric survey, a year before commencing preparations for the airborne geophysics, the team convened separate meetings with local farmers' associations, the Ikwezi Municipal Council and senior officials, to inform them in greater detail of the need for the magneto-telluric study and to officially welcome visiting German science collaborators (magneto-telluric survey team) from the GFZ-Potsdam.…”
Section: Landowner Suspicions and Trust Buildingmentioning
confidence: 99%
“…Our ongoing seismic experiments have also shown that ambient seismic noise, generated from pounding of ocean waves that surge the coast, can be used to map the subsurface virtually anywhere inland ( Figure 4c). This relatively new technique of tomography is based on cross-correlation of random diffuse ambient seismic signals, recorded between pairs of seismic stations, to approximate empirical Green's functions [32]. Green's function between two stations can be seen as a seismogram, recorded at one station from a source originating from another station.…”
mentioning
confidence: 99%